Interannual variation of sunspot magnetic fields from 1924 to 2004 - Lozitska, N.I. (Кинематика и физика небесных тел, 2005)
Some results of analysis of sunspot magnetic fields, including data from published papers (1000 measurements performed at the Mount Wilson National Observatory during 1924–1956) and data from various databases (20 000 measurements carried out during 1957–2004 at ten astronomical observatories, among them 400 measurements at the Kyiv University Astronomical Observatory) are presented. All the data were obtained using visual observations of the Zeeman splitting in the Fe I λλ 525.02 and 630.25 nm lines. The sunspots only with a diameter of penumbra from 30 to 60 arcsec and distance from disc centre less than 0.65R were studied. Magnetic field strengths Bsp averaged for each year were calculated on the basis of all individual daily measurements to exclude the influence of seasonal astroclimatic changes on quality of the Sun’s image and to reduce individual errors. The essential interannual variations of Bsp parameter in the range from 22 to 27 cT were found. These variations are about ten times more than standard errors of Bsp and have mainly an irregular character. The highest values of sunspot magnetic fields were in about 1943 and 2004 (Bsp ≈ 27 cT).